2018
DOI: 10.1080/14767058.2018.1489535
|View full text |Cite
|
Sign up to set email alerts
|

The application of near-infrared spectroscopy in oxygen therapy for premature infants

Abstract: NIRS objectively reflects the changes in oxygenation in the lung tissue. This study provides evidence for the clinical application of NIRS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 20 publications
1
22
1
Order By: Relevance
“…Regional tissue saturation by Near Infrared Spectroscopy (NIRS) is another noninvasive method which is gaining popularity. There is accumulating information based on NIRS studies especially in the fetal to neonatal transition and postnatal adaptation, and also on longterm safety and impact [17][18][19].…”
Section: Seminars In Fetal Andmentioning
confidence: 99%
“…Regional tissue saturation by Near Infrared Spectroscopy (NIRS) is another noninvasive method which is gaining popularity. There is accumulating information based on NIRS studies especially in the fetal to neonatal transition and postnatal adaptation, and also on longterm safety and impact [17][18][19].…”
Section: Seminars In Fetal Andmentioning
confidence: 99%
“…NIRS has been used in several studies to evaluate cerebral oxygenation and, to less extent, renal, hepatic, and splanchnic oxygenation 10–14 . However, although the penetration depth of 1.0−1.5 cm of the NIRS light 15 is appropriate for the study of the oxygenation of the lung parenchyma in preterm infants, this possible use has been poorly investigated 16 …”
Section: Introductionmentioning
confidence: 99%
“…Although NIRS has been commercially available as a clinical device since the early 1990s, there has been limited research on the use of NIRS to monitor respiratory function. A previous study found a positive correlation between pulmonary regional oxygen saturation (rSO 2 ) using NIRS and arterial partial pressure of oxygen (PaO 2 ) obtained from a blood gas analysis as a gold standard [ 34 ]. A wearable NIRS sensor provides several advantages over conventional methods for monitoring respiratory function.…”
Section: Discussionmentioning
confidence: 99%